Masalah Sosial Masyarakat Dalam Pementasan Drama Sang Pemikul Tandu Karya Gepeng Nugroho - Puspita, Erina; Humaira, Alma Khalisa (Indonesian Journal of Education and Development Research, 2025)
This study analyzes various social problems in the drama Sang Pemikul Tandu by Gepeng Nugroho using a sociological literary approach and Soekanto's theory of forms of social problems. This study aims to identify 9 (nine) forms of social problems depicted through the characters and storylines in the drama. The main data was taken from drama performances published on the Padepokan Seni Gubug Kebon YouTube channel. The research method used is a qualitative descriptive method with a documentation approach and recording techniques. The results of the study found several social problems including poverty, family disorganization, problems of the younger generation, and violations of community norms. This shows that the drama Sang Pemikul Tandu reflects the social reality that often occurs in society, where social injustice and other social problems are the main focus.